Factors affecting the parking problem at Seksyen 9, Shah Alam, Selangor / Noratikah Mazelan and Nor Azalina Yusnita Ab Rahman - Mazelan, Noratikah; Ab Rahman, Nor Azalina Yusnita (2018)
Car parking is viewed as a classic urban problem and getting worse by the day in Malaysia. It seems out of control when cities expand into townships. Parking problems can cause traffic congestion and obstruction as well as road bully incidents. The objective of this study is to determine the factors affecting parking problems at Seksyen 9, Shah Alam, Selangor. Such a study is important and timely especially in urban environments of new emerging townships whereby increase in new and inexperienced drivers each day and brisk vehicle sales are the main contributory factors to road congestion. The research was conducted via questionnaire survey related to insufficient parking bay, parking haphazardly, parking patterns, motorists' attitudes, and lack of enforcement, public transport services and safety. The outcomes of the study revealed that insufficient number of parking bays is the most important factor causing parking problems. This is due to the increased affordability to purchase vehicles since cars have become necessities nowadays. A few recommendations are suggested such as reviewing the parking planning policies, improving public transport and providing parking bay special privileges for local workers at the area. Future research should delve into the solutions taken by a few local authorities in Malaysia to solve the parking problems.